2017
DOI: 10.1007/s00262-017-1999-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implication of CD274 (PD-L1) protein expression in tumor-infiltrating immune cells for microsatellite unstable and stable colorectal cancer

Abstract: In this study, we investigated the clinical relevance of CD274 (PD-L1) protein expression by tumor cells and tumor-infiltrating immune cells in colorectal cancer (CRC). To this end, 186 microsatellite instability-high (MSI-H) and 153 microsatellite stable (MSS) CRCs were subjected to immunohistochemistry (IHC) analysis for the expression of CD274 and mismatch repair proteins. CD274 expression was evaluated in tumor cells at the center (TC) and periphery (TP), and immune cells at the center (IC) and periphery (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
50
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 43 publications
9
50
4
Order By: Relevance
“…The association between the expressions of PD‐L1, PD‐L2 and PD‐1 in TIMC and prognosis is controversial. Several possibilities have been considered . In salivary gland carcinomas, Mukaigawa et al and Harada et al examined PD‐L1 expression in TIMC and demonstrated that cases with positive PD‐L1 expression had a significantly unfavorable prognosis by Kaplan‐Meier method .…”
Section: Discussioncontrasting
confidence: 82%
“…The association between the expressions of PD‐L1, PD‐L2 and PD‐1 in TIMC and prognosis is controversial. Several possibilities have been considered . In salivary gland carcinomas, Mukaigawa et al and Harada et al examined PD‐L1 expression in TIMC and demonstrated that cases with positive PD‐L1 expression had a significantly unfavorable prognosis by Kaplan‐Meier method .…”
Section: Discussioncontrasting
confidence: 82%
“…Whereas immune cell-specific PD-L1 expression was found to be an independent prognostic factor, tumour cell-specific PD-L1 expression was not associated with survival neither in the full cohort nor in subgroup analysis according to PTL, supporting previous reports in CRC 16 , 17 , 19 , 22 and other cancers. 32-34 Nonetheless, an abundance of studies have reported high PD-L1 expression to be associated with an impaired prognosis due to induction of immune evasion, 6 , 7 , 35 being the rationale for PD-1/PD-L1 blockade.…”
Section: Discussionsupporting
confidence: 80%
“…17 , 19 , 22 Moreover, in subsite analysis according to PTL, PD-L1 expression was independently associated with a prolonged survival in patients with right-sided and left-sided colon cancers, but not in patients with rectal cancer. These findings further support previous evidence suggesting that proximal and distal CRC may represent different epidemiological, pathological, genetic, and clinical entities.…”
Section: Discussionmentioning
confidence: 92%
“…These findings might be attributed to a bystander effect of TIL infiltration; in fact, the number of PD‐L1‐positive TILs was associated with TIL density, implying that PD‐L1‐positive immune cells increased proportionally to the intratumoral immune reaction . However, Darb‐Esfahani et al reported that positive prognoses associated with PD‐L1‐positive TILs are independent of the number of T cells; in our previous study, there was no evidence that PD‐L1 expression was related to the density of TILs . The complex interaction between immune effector cells and the tumor microenvironment very likely impacts the biological significance of particular immune markers and also appears to be dependent on the tumor type.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies revealed an association between unfavorable clinical outcomes and tumoral PD-L1 expression in patients with CRC, 11,17,18 whereas other studies found no such associations. 9,19 Some researchers suggested that the prognostic implication of PD-L1 expression might depend on the mismatch repair status, 8,10 but the outcomes were inconsistent. Our own survival analysis showed that the expression of PD-L1 was correlated with poorer clinical outcomes in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%